Evaluasi Siklus Pelaksanaan Standar Dalam Sistem Penjaminan Mutu Internal (SPMI) Di STT Bethel Indonesia - Deni Trianto (UHN IGB Sugriwa Denpasar, 2020)
Evaluation of the standard implementation cycle in the Internal Quality Assurance System (SPMI) is very important, bearing in mind the standard implementation cycle in the Internal Quality Assurance System (SPMI) is a benchmark of how the commitment of tertiary institutions to achieve the expected quality of education. This research was conducted at the internal quality assurance unit at STT Bethel Indonesia. The method in this study is qualitative, and data collection techniques use direct observation, document and archive searches, and in-depth interviews. The results showed that (1) Implementation of standards in the Internal Quality Assurance System (SPMI) implemented by STT Bethel Indonesia used 24 National Higher Education Standards; (2) There has not been an equal commitment from all academicians to implement each standard in the Internal Quality Assurance System (SPMI) in order to create a better quality of education; (3) The still dominant cycle of standard implementation in the field of education can be seen from the standards that have already been carried out as many as five standards, while for research and community service standards the standards implemented have not reached half the set standards.